Development of a Small Scale Concentrating Parabolic trough Solar Collector for Drying Purposes - Khan, Muhammad Aamir; Rahman, M.; Hanif, M.; Israr, Muhammad Aamir; Shah, S. Fahad (Engineering International, 2013)
A high performance solar collector was developed to modify agricultural building environment such as dairy, poultry farm buildings and greenhouses. Moreover it should be efficiently utilized as a solar dryer for drying various agricultural products and by products. The materials used include steel sheet with high performance of reflecting light, absorber tube, and angle iron and fully insulated drying chamber. A CPTSC was a tilted at 340south (Equivalent to the latitude of Peshawar) Pakistan. A CPTSC a total reflecting surface area was 2.9 m2 respectively. The absorber tube having a surface of 0.376 m2 was fixed in front of the reflector at the distance equal to the focal length. The total volume of drying chamber was 0.3135 m3. An experiment was conducted to enhance the efficiency of the CPTSC and two air mass flow rate treatments were tested with normal and convective mass air flow rate, 0.6 kg. Min-1 and 1.72 kg. Min-1 under the average temperature of the month (January, February and March, 2012). Moreover, the process was replicated three times under the completely randomized design. The result showed that both air mass flow rate and average temperature of the month significantly effected the efficiency of a concentrating parabolic trough solar collector. The new model of a CPTSC increased the efficiency from 8 to 25 % with increase in both air mass flow rates and average temperature of the months. Therefore it is concluded that the solar collector efficiency increased with increasing air mass flow rate.
Keywords: Solar Energy; Solar Collector; Solar Drier and Collector Efficiency